2019
DOI: 10.1111/1758-2229.12739
|View full text |Cite
|
Sign up to set email alerts
|

Ontogeny of symbiont community structure in two carotenoid‐rich, viviparous marine sponges: comparison of microbiomes and analysis of culturable pigmented heterotrophic bacteria

Abstract: SummaryMarine sponges harbour diverse communities of microbes. Mechanisms used to establish microbial symbioses in sponges are poorly understood, and the relative contributions of horizontal and vertical transmission are unknown for most species. We examined microbial communities in adults and larvae of carotenoid‐rich Clathria prolifera and Halichondria bowerbanki from the mid‐Atlantic region of the eastern United States. We sequenced microbiomes from larvae and their mothers and seawater (16S rRNA gene seque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 82 publications
1
20
0
Order By: Relevance
“…The core microbiomes are characterized by generalists microbes with little representation of specialists, a pattern previously described as "specific mix of generalists" (Erwin et al, 2012a). Different sponge species likely represent different ecological niches for prokaryotes, each with a specific microbial community that is vertically and horizontally acquired and selectively maintained (Webster et al, 2010;Sacristán-Soriano et al, 2019). Host identity seems to be the strongest driving force in determining the composition of sponge symbiont assemblages.…”
Section: Resultsmentioning
confidence: 99%
“…The core microbiomes are characterized by generalists microbes with little representation of specialists, a pattern previously described as "specific mix of generalists" (Erwin et al, 2012a). Different sponge species likely represent different ecological niches for prokaryotes, each with a specific microbial community that is vertically and horizontally acquired and selectively maintained (Webster et al, 2010;Sacristán-Soriano et al, 2019). Host identity seems to be the strongest driving force in determining the composition of sponge symbiont assemblages.…”
Section: Resultsmentioning
confidence: 99%
“…Statistic differences for all the alpha-diversity metrics were observed between adults and larvae, between sponges (adults and larvae) and environmental samples (seawater and sediment) and between all the sample groups, with sediment microbiota being significantly different in relation to the other groups ( Figure 3 ; Table S3 ). The larvae microbiota has previously been reported to be less rich and less diverse than the microbial communities living in their respective parents for some demosponge species, such as Amphimedon queenslandica [ 27 ], and Clathria prolifera and Halichondria bowerbani [ 19 ]; however, the opposite has also been reported, for instance in the Great Barrier Reef sponge Rhopaloeides odorabile [ 16 ]. The higher microbial diversity here observed in the P. cyanorosea offspring may result from the deposition of environmental microorganisms on the surface of the non-feeding larvae [ 24 ], in particular during their later stages in sponge development, just before the release into the seawater environment.…”
Section: Discussionmentioning
confidence: 99%
“…With the increased application of next-generation sequencing (NGS) as the general approach in the characterization of sponge-associated microbial communities, it became clearer that the role that HT was playing in the establishment of sponge microbial community structures had been severally underestimated. From initial observations indicating the possibility of seawater as a “microbial seedbank” for sponges [ 16 ] to more recent studies supporting environmental acquisition as a major contributor to a functional sponge microbiome [ 17 , 18 , 19 ], HT has been progressively occupying a more central role, while the primary importance of VT has been called into question [ 20 ]. The replacement of “sponge-specific microbial clusters” [ 21 ] by the term “sponge-enriched microbial clusters” [ 22 , 23 ] together with the proposal of mechanistic models involving interplay between both VT and HT modes [ 24 , 25 , 26 , 27 ] are indications of how these changing views are progressively converging into the concept of a mixed mode of microbiome transmission for the sponge holobiont.…”
Section: Introductionmentioning
confidence: 99%
“…Following the previous assumptions of symbiont species‐specificity (Turon et al ., 2018; Björk et al ., 2019), Sacristán‐Soriano and colleagues (2019) found that the microbial consortia of adults and larvae in two north‐eastern Atlantic sponges presented a taxonomic composition and structure significantly different from seawater: less than 15% of the OTUs transmitted from parents to their offspring originated from water. The authors proposed that the larval microbiome is driven by host processes where the parental sponge could still restrain the symbiont passage to the larvae at earlier developmental phases.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the microbiome in the adult phase is defined by active invasion, colonization and, ultimately, the establishment of environmental microorganisms in the sponge tissues. The authors also found that the host species constituted the main factor underlying the microbiome variation between sponges (Sacristán‐Soriano et al ., 2019).…”
Section: Introductionmentioning
confidence: 99%